Selective screening procedure for the isolation of heat- and cold-sensitive, DNA replication-deficient mutants of bacteriophage SPO1 and preliminary characterization of the mutants isolated. - Glassberg, J (1977)
A procedure is described for the selective isolation of temperature-sensitive replication-deficient mutants of Bacillus subtilis phage SPO1. A modification of the procedure permits the isolation of temperature-sensitive mutants in specific cistrons of interest. The applicability of these procedures to other viral systems is discussed. The mutations isolated were assigned to eight replication-deficient cistrons, with the cold-sensitive mutations showing a distribution strikingly different from that of the heat-sensitive mutations. As a preliminary to the identification of initiation-deficient mutants, the mutants were divided into three classes on the basis of their ability to synthesize DNA after a shift to nonpermissive temperature. We also report two incidental results: (i) the SPO1 dUMP hydroxymethylase, like the T4 dCMP hydroxymethylase, may be part of a multifunctional complex; and (ii) mutants were isolated that were replication positive but lysis deficient and failed to complement one of the replication-deficient mutants.